2013
DOI: 10.1088/0957-4484/24/9/095707
|View full text |Cite
|
Sign up to set email alerts
|

Subsurface synthesis and characterization of Ag nanoparticles embedded in MgO

Abstract: Metal nanoparticles exhibit a localized surface plasmon resonance (LSPR) which is very sensitive to the size and shape of the nanoparticle and the surrounding dielectric medium. The coupling between the electromagnetic radiation and the localized surface plasmon in metallic nanoparticles results in a sizable enhancement of the incident fields, making them possible candidates for plasmonic applications. In particular, partially exposed metallic nanoparticles distributed in a dielectric matrix can provide prime … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…Figure 1 illustrates distinctly the whole process of the nucleation and growth of faceted precipitates during post-implantation annealing, which provides a lot of useful information to comprehend the mechanism of the precipitation. Similar experimental observations about the formation and evolution of precipitates with characteristic shape in the literatures 5,6,24 confirm the availability of our simulation results. In order to explore the influence of ion dose on the kinetics of nucleation and growth of precipitates, different ion doses of implantation are calculated by changing the values of c i in Eq.…”
Section: Resultssupporting
confidence: 91%
“…Figure 1 illustrates distinctly the whole process of the nucleation and growth of faceted precipitates during post-implantation annealing, which provides a lot of useful information to comprehend the mechanism of the precipitation. Similar experimental observations about the formation and evolution of precipitates with characteristic shape in the literatures 5,6,24 confirm the availability of our simulation results. In order to explore the influence of ion dose on the kinetics of nucleation and growth of precipitates, different ion doses of implantation are calculated by changing the values of c i in Eq.…”
Section: Resultssupporting
confidence: 91%
“…Building upon this work, Cerezo et al [10], followed by Blavette et al [11], and finally Kelly et al [12] developed a technique currently known as atom probe tomography (APT). APT provides analytical, three-dimensional mapping of a range of solid materials [11,[13][14][15][16][17][18][19][20][21][22][23][24][25] with near-atomic resolution.…”
Section: Introductionmentioning
confidence: 99%
“…Even though such studies have investigated the nature of coke formed during ethanol conversion reactions at a bulk average level or at a macroscopic level, nanoscale imaging of the carbonaceous molecules present in spent catalyst materials using depth profiling is lacking in the literature. Recently, a relatively new characterization capability called atom probe tomography (APT) has been increasingly used to perform 3D quantitative analysis of element distribution in catalyst materials with sub-nanometer–scale spatial resolution and high mass sensitivity up to the few parts per million level of concentration of elements in materials2627282930313233. It has also been demonstrated that APT can be used to quantitatively image the Al distribution in zeolite materials, and evidence for changes in Al distribution can be obtained by comparing results before and after severe steam treatment of HZSM-5 at 700 °C34.…”
mentioning
confidence: 99%